Ivabradine induces RAD51 degradation, potentiating PARP inhibitor efficacy in non-germline BRCA pathogenic variant triple-negative breast cancer - Ho Tsoi; George Man Hong Leung; Ellen Pui Sum Man; Chan Ping You; Koei Ho Lam Cheung; Kelvin Yuen Kwong Chan; Chun Gong; Michael Shing Yan Huen; Ui Soon Khoo (Journal of Translational Medicine)
Abstract Background Triple-negative breast cancer (TNBC) is an aggressive subtype lacking targetable proteins for treatment. PARP inhibitors (PARPi) are effective in BRCA-mutated cancers but have limited utility in non-germline BRCA-mutated (non-gBRCAm) TNBC. We hypothesized that inducing BRCAness by targeting RAD51, a key homologous recombination protein, could sensitize non-gBRCAm TNBC to PARPi. Methods EGFP-tagged RAD51 was generated and EGFP signal was monitored for identifying agents that affected RAD51 protein expression and stability. Cell viability was assayed using cell counting kit-8. Synergism of ivabradine and olaparib was determined using SynergyFinder 3.0. DR-GFP, EJ5-GFP and comet assays were employed to evaluate the degree of DNA repair and damage, respectively. Protein and mRNA levels were determined by western blot and qPCR, respectively. ChIP was used to determine the binding to ATF6 to the promoter of FBXO24. CoIP was employed to determine the interaction between RAD51 and FBXO24. Xenografts on nude mice and PDTX were in vivo models for validating the combined effect of ivabradine and olaparib. Results Using an EGFP-RAD51 reporter, we identified ivabradine as a RAD51-reducing agent. In vitro studies with TNBC cell lines demonstrated that ivabradine synergized with PARPi to reduce cell viability (ZIP score > 10), induce apoptosis, and impair HR-mediated DNA repair. This synergy was confirmed in vivo using xenografts and patient-derived tumor xenografts, where co-treatment with clinical grade ivabradine (Coralan) and PARPi olaparib (Lynparza) led to substantial tumor growth inhibition without notable toxicity. Mechanistically, ivabradine triggered ER stress, activating ATF6 to upregulate FBXO24-dependent ubiquitination, leading to RAD51 degradation, resulting in the condition of BRCAness. Chromatin immunoprecipitation and co-immunoprecipitation confirmed the ATF6-FBXO24-RAD51 cascade. These findings reveal a novel mechanism by which ivabradine, an FDA-approved cardiac drug, induces BRCAness, by degrading RAD51 via the ATF6-FBXO24 axis, thus, by mimicking HR deficiency hypersensitizes BRCA-proficient TNBC to olaparib. Conclusion This study highlights the translational potential of repurposing ivabradine as a therapeutic strategy for non-gBRCAm TNBC. By addressing a critical unmet need of this aggressive breast cancer subtype, it can potentially expand the utility of PARPi. Graphical abstract Schematic diagram illustrates the synergistic effect of IVA and OLA. IVA treatment results in enhanced ER stress, leading to the activation of ATF6. The activated ATF6 translocates to the nucleus and binds to the promoter of FBXO24 to induce its expression. FBXO24 mediates RAD51 protein degradation via the ubiquitin-proteasome system. The reduction of RAD51 expression contributes to the feature of BRCAness. Adding PARP inhibitor OLA can prevent single-strand DNA damage from repairing, subsequently becoming DNA double-strand breakage (DSB). The low expression of RAD51 mediated by IVA compromises the mechanism for repairing DSB via HR, leading to the accumulation of DSB. Eventually, cell death is induced.